Factors associated with level of physical activity among elderly in Klinik Rawatan Keluarga (KRK), Hospital Universiti Sains Malaysia - Suhaini, Norfarihah Mohammad (Universiti Sains Malaysia, 2013)
Physical activity is one of the most basic human functions. As we grow older, staying physically active is vital for successful ageing process. The numerous benefits of physical activity for health and longevity among elderly are well established. However, despite this knowledge, many elderly are much less active than desired and too few people engage in regular physical activity. The study is purposely to determine the level of physical activity among elderly clients in Klinik Rawatan Keluarga (KRK), Hospital USM. Apart from that, it is conducted to determine the factors associated with level of physical activity among elderly in KRK. Data collected using interview method and selfadministered questionnaire which were distributed to the respondents by non-probability, convenience sampling method. 158 elderly were recruited as respondents, with an age range between 60 and 80 years old. The level of physical activity in elderly was measured using Physical Activity Scale for Elderly (PASE) instrument. Statistical analysis carried out using SPSS program version 20.0, with the p-value of 0.05 for Chi-Square Test The result indicated that 50.0% of the respondents presented with low level of physical activity and 50.0% respondents had moderate level of physical activity. The mean PASE score of the elderly respondents was 154.64 (SD=58.49). The most common activities were household activity with the highest mean score 105.28 (35.40), compared to the leisure time activity 20.12 (15.48) and work-related activity 29.24 (40.77). Selected socio-demographic data which have a significant association with the level of physical activity is sex (p<0.001). Sex is related physical activity level because women were reported more likely to engaged in household activity. Besides that, the most commonly reported perceived barrier to physical activity identified by the majority of the respondents was ‘lack of time’. Nevertheless, the study also found that there were four barriers emerged as being statistically associated with physical activity level among elderly, which are ‘feel too old’, ‘lack of time’, ‘dislike exercising’ and ‘feel too tired’. The researcher concluded that the elderly in the sample study was not achieved the high level of physical activity. The elderly need to be encouraged for enhancing their physical activity as it is beneficially for them.